The Role of HSP90 in Preserving the Integrity of Genomes Against Transposons Is Evolutionarily Conserved - Specchia, Valeria (Cells, 2021)
The HSP90 protein is a molecular chaperone intensively studied for its role in numerous cellular processes both under physiological and stress conditions. This protein acts on a wide range of substrates with a well-established role in cancer and neurological disorders. In this review, we focused on the involvement of HSP90 in the silencing of transposable elements and in the genomic integrity maintenance. The common feature of transposable elements is the potential jumping in new genomic positions, causing chromosome structure rearrangements, gene mutations, and influencing gene expression levels. The role of HSP90 in the control of these elements is evolutionarily conserved and opens new perspectives in the HSP90-related mechanisms underlying human disorders. Here, we discuss the hypothesis that its role in the piRNA pathway regulating transposons may be implicated in the onset of neurological diseases.